MMS Observations of Harmonic Electromagnetic Ion Cyclotron Waves. Issue 17 (12th September 2018) - Usanova, M. E.; Ahmadi, N.; Malaspina, D. M.; Ergun, R. E.; Trattner, K. J.; Reece, Q.; Leonard, T.; Fuselier, S. A.; Torbert, R. B.; Russell, C. T.; Burch, J. L.
Abstract: Harmonically related electromagnetic ion cyclotron waves with the fundamental frequency near the double oxygen cyclotron frequency were observed by the MMS spacecraft on 18–20 May 2016. The wave activity lasted for three days, detected by the spacecraft on their consecutive inbound passages through the Earth's plasma sheet boundary layer. The waves were seen in both magnetic and electric fields, formed by over 10 higher order harmonics. Simultaneous ion flux measurements show the presence of ion ring distributions suggesting the energy source for the observed waves. The ion cyclotron harmonics were observed together with broadband waves extending from ~Hz to ~kHz frequency range, ion and electron phase space holes, and chorus waves. During some intervals, there is a clear modulation of chorus wave packets at the ion cyclotron fundamental harmonic frequency. These observations are particularly interesting since they suggest cross‐frequency and cross‐species coupling between processes happening on ion and electron scales. Plain Language Summary: We presented an example oxygen harmonic wave event observed by the MMS spacecraft in the morning magnetosphere. The observed harmonic waves are transverse electromagnetic and propagate almost parallel to the background magnetic field at lower harmonics and become electrostatic at higher harmonics. Energetic ion measurements show enhanced approximately a few keV H + and O + fluxes and the presence of H + and O + ring distributions suggesting that the wave energy source for the observed waves is provided by these distributions. Harmonics were accompanied by higher frequency broadband waves extending from ~Hz to ~kHz frequency range, ~ms spikes in the electric field and chorus waves. The latter were modulated at the fundamental frequency of the ion cyclotron harmonic wave. These observations are particularly interesting since they suggest cross‐frequency and cross‐species coupling between kinetic plasma processes happening on ion and electron scales. Key Points: Harmonic ion cyclotron waves with the fundamental frequency near the double oxygen cyclotron frequency were observed in the plasma sheet boundary layer The presence of H + and O + ring distributions suggests that the wave energy source for the observed waves is provided by these distributions There is a clear modulation of simultaneously observed chorus wave packets at the ion cyclotron fundamental harmonic frequency